Propostas educacionais e assistenciais de uma instituição de surdos localizada no interior de São Paulo: relato de profissionais - Lima, Larissa Chaves (Universidade Federal de São Carlos, 2021)
This study aims to analyze how the Institution located in the interior of the State of São Paulo promotes the social inclusion of deaf subjects through the teaching of Libras and the Portuguese Language, investigating their teaching-learning strategies and the interaction of the subjects in this process, from the perspective of the study of language, from the theories of Vygotsky and Bakhtin.Vygotsky's main theoretical contributions that can be correlated with the teaching of deaf people emphasize the understanding that happens in the proximal development, which demands the interaction between a more experienced and skilled person in the subject and someone who will learn. Being very important this interaction with teachers, interpreters and family members, in addition to socializing with deaf people that are fluent in Libras. In this context, Bakhtin reinforces that language development is based on a dialogic structure, and that it requires constant social interaction. For the methodological procedure of this study, interviews were conducted with two Institution professionals: a teacher and Libras instructor and a social worker in a semi-structured way through the Google Meet application, both lasting around forty minutes. In this sense, Institution presents its pedagogical and care proposal aligned with the development of language, so that the deaf not only acquire learning, but also expands their socialization, both within the family, by emphasizing the necessary literacy of parents, as well as in social interaction. with their peers, in encounters between deaf people with different levels of learning and expression. There is a need to diversify educational approaches, since deaf people have different levels of literacy, socialization, and also tend to acquire homemade signs, which makes the work of a personalized nature, according to the context of each student. Institution has a multi-professional team, which, even in the face of various challenges, such as the pandemic, seeks to maintain active work, remotely, so as not to harm the performance and social development of students.
Educational and care proposals of institution for the deaf located in the interior of São Paulo: professionals reports
Keywords: Língua de sinais; Libras; Desenvolvimento de linguagem; Sign languages; Libras; Language development; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO